2011
DOI: 10.1002/adem.201000292
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Connectivity of Rigid Phases on Strength of AlSi Alloys

Abstract: The load carrying capacity of the eutectic Si in AlSi alloys depends on its volume fraction, distribution, morphology and connectivity, namely its internal architecture. This can be modified by heat treatment at temperatures close to the eutectic point causing the spheroidisation and loss of connectivity of the eutectic Si. This decreases the load carrying capacity of the eutectic Si and, consequently, the room and high temperature strength of AlSi alloys is reduced. The presence of other phases such as cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 78 publications
1
27
0
1
Order By: Relevance
“…The eutectic Al-Si based casting alloys are widely used in automotive applications (E.g., piston production) due to their good castability, high strength, light weight, good wear resistance and low thermal expansion [1][2][3][4] . However, it is well-known that the pistons are working under very extreme and complicated environment, and the materials used for pistons should be able to withstand the temperatures from 350 to 400 o C, Therefore, the superb high temperature (HT) strength of such alloys is the important design criteria [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…The eutectic Al-Si based casting alloys are widely used in automotive applications (E.g., piston production) due to their good castability, high strength, light weight, good wear resistance and low thermal expansion [1][2][3][4] . However, it is well-known that the pistons are working under very extreme and complicated environment, and the materials used for pistons should be able to withstand the temperatures from 350 to 400 o C, Therefore, the superb high temperature (HT) strength of such alloys is the important design criteria [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…The strength of cast Al-Si piston alloys is given by the strength of the age-hardenable α-Al matrix and the load carrying capability of interconnected 3D hybrid networks formed by Si and various intermetallic phases [1,2,3,4,5]. The alloying elements Cu and Mg play a decisive role on precipitation strengthening of the matrix, while, together with Ni, they define the interconnectivity of the 3D networks [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon particles play a key role in the solidification, microstructural development and fracture processes of Al-Si-based alloys [1][2][3][4][5][6][7][8][9]. When these alloys are mechanically strained, it is typically observed that silicon particles within the a-aluminium matrix start fracturing gradually, essentially as soon as the alloy starts to deform plastically.…”
Section: Introductionmentioning
confidence: 99%